Presentation of gender dysphoria: A perspective from Eastern India - Sanyal, Debmalya (Indian J Endocrinol Metab, 2016)
CONTEXT: There is paucity of scientific data from India on gender identity disorders (GIDs) or gender dysphoria (GD). AIMS: To study the clinical, biochemical profile, personality characteristics and family support of GID subjects. SETTINGS AND DESIGN: A retrospective and cross-sectional study at an endocrine referral center in Kolkata in Eastern India between 2010 and 2015. SUBJECTS AND METHODS: Seventy-three GID subjects who presented to the center were included in the study. Clinical, biochemical profile, personality characteristics (cross-dressing), and family support were investigated. The protocol was presented to the Ethics Committee who felt that given the retrospective nature of the study, informed consent could be dispensed with. GD was diagnosed by Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition). STATISTICAL ANALYSIS USED: Unpaired t-test has been used to find the significance of study parameters between two groups of patients. Chi-square/Fisher Exact test has been used to find the significance of study parameters on categorical scale between two groups. RESULTS: Out of the total 73 patients, 55 (75.34%) patients were male-to-female and remaining 18 (24.66%) were female-to-male. Around 11% of GD subjects practiced cross-dressing. In spite of median age of onset of GD was 9 years, the mean age of GD at presentation was quite late at 25.77 ± 6.25 years due to lack of social and informative support. It is difficult for transgender to express their sexual identity in family or in society as only 10.96% of our GD subjects had family support, leading to delayed presentation and delayed endocrine consultation. This delayed endocrine consultation have accounted for a significant proportion of GD subjects having unplanned and ill-timed castration (16.36%) or mastectomy (16.67%) even by nonmedically qualified person (66.7% of castrated subjects). All GD subjects had normal thyroid stimulating hormone, testosterone, estradiol, and karyotype concordant with their biological sex. No significant differences were demonstrated between any of the studied parameters namely age at presentation, onset-age of GD, hormone profile, family support, and cross-dressing preferences. CONCLUSIONS: Social taboo and lack of informative, family support leads to delayed medical consultation and have accounted for complexities in presentation indicating a huge need of awareness programs in our country. Social and informative support can be improved by awareness programs, which might lead to an early endocrine evaluation and proper treatment with improved outcomes.